Tinjauan Siyasah Dusturiyah Kerhadap Putusan Mk Nomor 60/PUU-XXII/2024 Tentang Ambang Batas Pencalonan Kepala Daerah pada Pilkada 2024 - Ramadhan, Dimas Aji; Saebani, Beni Ahmad; Sutiana, Yana (Dinasti Research, 2025)
Constitutional Court Decision Number 60/PUU-XXII/2024 provides a new interpretation of the provisions on the threshold for nominating regional heads in Article 40 paragraph (3) of Law Number 10 of 2016, which previously limited non-parliamentary political parties from nominating regional head candidates even though they obtained valid votes. This study aims to analyze the normative correction from a legal perspective. This study uses a juridical-normative and qualitative-contextual approach with a library research method through an analysis of the Constitutional Court's decision, the principles of legal principles, and constitutional law literature. The results of the study show that the Constitutional Court's decision eliminates forms of electoral discrimination by restoring the rights of political parties that obtain 25% of valid votes to continue to nominate regional head candidate pairs, even without DPRD seats. In a legal perspective, this constitutional interpretation is in line with the principles of justice (al-adl), political equality (al-musawah), and public welfare (al-maslahah al-'ammah). This decision is considered as a form of ijtihad siyasiy by state institutions to free political access from the domination of local oligarchy. Thus, the constitution and Islamic principles can synergize in encouraging substantive democracy at the local level.